2019
DOI: 10.1038/s41467-019-13242-x
|View full text |Cite
|
Sign up to set email alerts
|

SERS discrimination of single DNA bases in single oligonucleotides by electro-plasmonic trapping

Abstract: Surface-enhanced Raman spectroscopy (SERS) sensing of DNA bases by plasmonic nanopores could pave a way to novel methods for DNA analyses and new generation single-molecule sequencing platforms. The SERS discrimination of single DNA bases depends critically on the time that a DNA strand resides within the plasmonic hot spot. In fact, DNA molecules flow through the nanopores so rapidly that the SERS signals collected are not sufficient for single-molecule analysis. Here, we report an approach to control the res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(173 citation statements)
references
References 63 publications
(77 reference statements)
1
154
2
1
Order By: Relevance
“…Pioneering studies from different groups have demonstrated the capability of identifying DNA or RNA fragments and even individual nucleobases by SERS. [ 280,281 ] Moreover, recent theoretical and experimental studies have demonstrated that the spatial resolution of SERS approaches the subnanometer level in dry conditions. Researchers also demonstrated remote excitation and detection of SERS using optical nanoantenna (nanowire‐nanoparticle system, single nanowire system, crossed nanowire system, nanowire‐dimer system, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Pioneering studies from different groups have demonstrated the capability of identifying DNA or RNA fragments and even individual nucleobases by SERS. [ 280,281 ] Moreover, recent theoretical and experimental studies have demonstrated that the spatial resolution of SERS approaches the subnanometer level in dry conditions. Researchers also demonstrated remote excitation and detection of SERS using optical nanoantenna (nanowire‐nanoparticle system, single nanowire system, crossed nanowire system, nanowire‐dimer system, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…However, there is still a long way to go, with many details remaining to be addressed. [9,90] For example, the translocation speed of molecules is still too fast for a spectrometer. Finally, it needs to be mentioned that plasmons can also modulate the FRET between a donor fluorophore and an acceptor fluorophore.…”
Section: Detection Of Plasmon Resonance Shift Sersmentioning
confidence: 99%
“…In the “flow-through” SERS, molecules pass the detection point so rapidly that the collected SERS signals are not sufficient for single-molecule analysis. By employing a single nanopore [ 54 ] or nanoslit [ 55 ] that allows the electrokinetic capture (i.e., electroplasmonic trapping effect) to increase the residual time of target molecules within the hot-spots, as illustrated in Figure 2 b, it is possible to trace the spectroscopic fingerprinting of a single DNA molecule. The device has also been applied in detection of all four DNA bases in a single DNA molecule, as well as in identification of single nucleobases in a single oligonucleotide.…”
Section: Optical Detectionmentioning
confidence: 99%
“…The device has also been applied in detection of all four DNA bases in a single DNA molecule, as well as in identification of single nucleobases in a single oligonucleotide. The above-mentioned results indicate the capability of nanofluidics in manipulating single molecules, as well as the light–matter interactions for single-molecule detection [ 54 , 55 ].…”
Section: Optical Detectionmentioning
confidence: 99%
See 1 more Smart Citation